2017
DOI: 10.18203/2394-6040.ijcmph20175794
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of self-care practices among hypertensive patients: a clinic based study in rural area of Singur, West Bengal

Abstract: Background: Hypertension, also known as high blood pressure is a global public health concern. It is an important modifiable risk factor for cardiovascular disease and stroke. It remains silent, being generally asymptomatic during its clinical course and it accounts for a large proportion of cardiovascular deaths; lifestyle modification is the first line of intervention for all patients with hypertension, yet it was never been empirical. The aim of the study was to assess the pattern of self-care practices, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
29
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 5 publications
10
29
3
1
Order By: Relevance
“…Respondents who had an educational status of college and above had 4.21 [AOR = 4.21, 95% CI 1.304–13.559, p = 0.016] more good self-care practice than those who cannot read and write. This is in line with the study conducted in India [17]. Having good educational status helps individuals to have good knowledge and thus promotes respondents’ good self-care practices.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Respondents who had an educational status of college and above had 4.21 [AOR = 4.21, 95% CI 1.304–13.559, p = 0.016] more good self-care practice than those who cannot read and write. This is in line with the study conducted in India [17]. Having good educational status helps individuals to have good knowledge and thus promotes respondents’ good self-care practices.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the availability of anti-hypertensive drugs and optimal hypertension self-care practices are proved to decrease BP and all cause mortality rate and cardio-vascular morbidities [15, 16], hypertensive patients are suffering from unfavorable self-care practices. Many studies have shown that hypertensive patients have poor self-care practices [1721].…”
Section: Introductionmentioning
confidence: 99%
“…However, the finding of our study was lower than studies done in Dessie Town, Ethiopia, which was 49% 27 and 37% in a study conducted in West Bengal. 41 The observed difference may be attributed to the difference in data collection instruments used between studies. For instance, the study done in Dessie Town used a hypertensive self-care practice tool containing 20 items each rated four points in Likert-type scale points.…”
Section: Discussionmentioning
confidence: 99%
“…Different finding encourage compliance with hypertension self-care practice such as weight reduction, smoking cessation, low salt diet, and physical activity can contribute to controlling blood pressure [8,9]. A clinic based study in rural area of Singur, West Bengal revealed that primary level education, poor socio economic status, widow/separated and people with self-perceived poor health status had significant association with unfavorable self-care practices [10].…”
Section: Introductionmentioning
confidence: 99%